The Efficiency of Public Services and the Level of Sufficiency Economy of the Local Administrative Organizations in the Northern Region of Thailand: ประสิทธิภาพการให้บริการสาธารณะกับระดับความเป็นเศรษฐกิจพอเพียง ขององค์กรปกครองท้องถิ่นภาคเหนือ - Nonthakhot, Phanin; Somyana, Wirasak (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อประเมินประสิทธิภาพการให้บริการสาธารณะกับระดับความเป็นเศรษฐกิจพอเพียงขององค์กรปกครองท้องถิ่น (อปท.) จำนวน 42 แห่ง 4 จังหวัด ได้แก่ เชียงใหม่ ลำพูน อุตรดิตถ์ และพิษณุโลก ใช้วิธี Data Envelopment Analysis (DEA) เป็นเครื่องมือในการวิเคราะห์ประสิทธิภาพการดำเนินงานในกรณีที่มีปัจจัยการผลิตและผลผลิตหลายชนิด โดย อปท. ในพื้นที่ดังกล่าวมีการประยุกต์ใช้แนวทางปรัชญาของเศรษฐกิจพอเพียงในชุมชนของตนเอง 7 ด้านของการให้บริการสาธารณะ ได้แก่ ด้านการบริหารจัดการองค์กร ด้านการเกษตร ด้านธุรกิจชุมชน ด้านสุขภาพ อนามัยและสิ่งแวดล้อม ด้านสังคมและวัฒนธรรม ด้านทรัพยากรชุมชน และด้านการทำแผนพัฒนาชุมชนแบบมีส่วนร่วม ผลการวิจัยสรุปได้ว่าความสัมพันธ์ระหว่างประสิทธิภาพการให้บริการสาธารณะกับระดับความเป็นเศรษฐกิจพอเพียงของ อปท. เป็นไปในทิศทางเดียวกัน โดยเฉพาะประสิทธิภาพในการให้บริการสาธารณะด้านการบริหารจัดการองค์กร (ร้อยละ 99.12) และด้าน การทำแผนพัฒนาชุมชนแบบมีส่วนร่วม (ร้อยละ 94.44) ส่งผลให้ อปท. มีระดับความเป็นเศรษฐกิจพอเพียงได้สูงขึ้น และเมื่อเปรียบเทียบประสิทธิภาพในการให้บริการตามระดับความเป็นเศรษฐกิจพอเพียงของ อปท. ในระดับเข้าข่าย ระดับเข้าใจ และระดับเข้าถึง พบว่า อปท.ที่มีระดับความเป็นเศรษฐกิจพอเพียงระดับเข้าใจและเข้าถึง มีประสิทธิภาพในการให้บริการด้านบริหารจัดการองค์กร ด้านการทำแผนพัฒนาชุมชนแบบมีส่วนร่วม ด้านสังคมวัฒนธรรมและการเรียนรู้ และด้านการเกษตร (อินทรีย์) ผลการศึกษาดังกล่าวนี้สะท้อนให้เห็นว่าประสิทธิภาพของการให้บริการสาธารณะของแต่ละอปท. มีความแตกต่างกัน ทำให้ผู้บริหารและเจ้าหน้าที่ทราบความสามารถของตนเอง และเป็นหนึ่งในแรงจูงใจสำคัญที่ทำให้ตระหนักถึงความสำคัญของการบริหารงบประมาณให้มีประสิทธิภาพมากขึ้น ABSTRACT This research was to analyze the efficiency of public services and the level of the sufficiency economy of local administrative organizations of 42 organizations in 4 provinces (Chiang Mai, Lamphun, Uttaradit and Phitsanulok). The analysis approach in this study was conducted using the data development analysis program (DEAP) as the analysis tool because there was no need to specify the function form, and it suited the efficiency measure with multiple inputs and outputs. There were seven main aspects of the applications of the sufficiency economy philosophy used by local administrative organizations, which are as follows: 1) organizational administration and management; 2) agriculture; 3) community businesses; 4) health, sanitation, and environment; 5) society and culture; 6) community resources; and 7) participatory planning for community development. The results revealed that the public service efficiency and the level of sufficiency economy of the organizations were correlated, especially organizational management and administration (99.12%) and participatory community development planning (94.44%). These results are highly important because any local administrative organizations with a high percentage of these two aspects (efficiency value higher than 90%) would have a higher level of sufficiency economy. After relating the service efficiency of sub-district administrative organizations to the levels of the sufficiency economy philosophy, which were qualify level (an organization for sustainability), an understandable level (an organization for happiness), and an approachable level (an organization for benefit and happiness), it was found that the local administrative organizations at the understandable level or organization for happiness had service efficiency in the organizational administration and management aspect, the social, cultural, and learning aspect, and the organic agricultural aspect. It can be concluded that the levels of success of each aspect were different according to the level of the understanding of each organization. The fact that the effectiveness of public services provided by each local administrative organization is different can make the local administrative organizations realize their competency and this can be one of the factors that make them aware of the importance of how to manage their budget more efficiently.